Conservation Education Media: Birdwatching Guidebook in the Buffer Zone of the Rawa Danau Nature Reserve - Leksono, Suroso Mukti; Marianingsih, Pipit; Dewi, Nurul Aulia; Cahya, Nur (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
Rawa Danau Nature Reserve is a conservation area that protects various remaining flora and fauna on Java island, including birds. However, at present, Rawa Danau Nature Reserve 's existence is threatened due to changes in the structure and habitat function by the activities of the surrounding community. Therefore, it is necessary to have a solution in the form of efforts to preserve and preserve the diversity of species and their ecosystems. One form of this program is conservation education. Conservation education is a form of effort to protect biodiversity and natural resources by increasing knowledge, skills, participation, attitudes, and awareness of the importance of natural resources to sustain life. Information media is needed to facilitate the achievement of conservation education goals, one of which is the development of a birdwatching field guidebook. This study aimed to develop a birdwatching field guidebook as a medium for conservation education in the Rawa Danau Nature Reserve area The development method was used to create the field manual. The developed guidebook contains information on bird diversity, bird conservation, observation techniques, and bird observation locations, as well as bird identification sheets accompanied by bird distribution patterns in the form of descriptions and illustrative pictures or photographs of research results. The book was also developed to meet the principles of environmental education, namely to develop awareness, knowledge, attitudes, skills, and participation in protecting the environment.